Redesigning English For Specific Purpose (Esp) Curriculum To Pre-Service Teachers Of Primary Education Department At STKIP Muhammadiyah Bangka Belitung - Pratiwi Amelia (Pascasarjana Universitas Negeri Semarang, 2019)
This paper aims to design English for Specific Purposes (ESP) curriculum to pre-service teachers under Primary Education Department of STKIP Muhammadiyah Bangka Belitung (STKIP MBB), Pangkalpinang, Indonesia. Based on observation and need analysis, there are no specific English materials of teaching which enables the learners to participate actively based on their socio-cultural context. The English course which is taught to the students were general English without specific consideration when designing its curriculum. The writer is eager to redesign the English course by following the Common European Framework (CEFR) provided by the European Council and also implement the language curriculum design and socialization by Mickan, Peter (2013) and Macalister, J and Nation (2010). It is hoped that this curriculum would be beneficial to the students and it can be used as one of model on teaching English as Second Language for specific purpose.